Jump Risk Contagion Under Regime Switching: An Empirical Analysis Based on the CSI 300 Index and the Hang Seng Index - Hongjun Duan; Hui Wang; Yifeng Wang (Discrete Dynamics in Nature and Society)
The jump in the value of the stock may result in a corresponding escalation of risk associated with the stock market. When a jump occurs in any particular market, such a risk can spread to other markets. This paper examines realized volatility and risk contagion of the jump between the Chinese mainland and Hong Kong market utilizing realized volatility and three realized jump separation methods. Correspondingly, the Markov regime-switching approach is employed to exhibit the contagion effect of the jump risk in two economic states. This study employs the Shanghai–Shenzhen 300 Index and the Hang Seng Index as empirical research subjects. The results show that the Hong Kong market has a higher frequency of jumps compared to the mainland market. The MedRV method is found to be effective in identifying more jumps, while the mainland market displays a unidirectional contagion effect on Hong Kong. Under such circumstances, the risk associated with a continental market jump exhibits an unevenly contagious effect on the Hong Kong market. In conclusion, China needs to enhance its financial market risk management in order to avert the spread of escalating risk across markets.